Editorial - Hayes, Grahame (PINS-Psychology in Society, 2026)
The organisation of psychology has been a very vexed issue in South Africa. It has mostly been contained within the politics surrounding professional organisations. The history of the politics of association in psychology has been dominated by the conflict and debate between SIRSA, SAPA, and PASA. In other words, the history of the organisation of psychology in South Africa has been inextricably linked to apartheid ideology and discourse. This had made it difficult for other organisations and groups to penetrate this reactionary hegemony. OASSSA (Organisation for Appropriate Social Service in South Africa), the predominantly black constituency of the "Psychology and apartheid" group, and even this journal PINS have been "outside" of the mainstream of defining the nature and practice of psychology.